Comparison of hematopoietic stem cell transplantation and immunosuppressive therapy as the first-line treatment option for patients with severe hepatitis−associated aplastic anemia - Zhang, Xiaoyu; Yang, Wenrui; Yang, Donglin; Wei, Jialin; Zhang, Ping; Feng, Sizhou; Jiang, Erlie; Zhang, Li; He, Yi; Zhang, Fengkui; Han, Mingzhe (Frontiers in Immunology, 2023)
Hepatitis-associated aplastic anemia (HAAA) is a rare variant of acquired aplastic anemia characterized with a syndrome of bone marrow failure after hepatitis. We retrospectively analyzed the outcomes of consecutive severe HAAA patients who received immunosuppressive therapy (IST, n = 70), matched-sibling donor hematopoietic stem cell transplantation (MSD-HSCT, n = 26) or haploidentical-donor (HID) HSCT (n = 11) as the first-line treatment. In the IST group, the hematologic response (HR) rate was 55.71% at 6 months. In contrast, HSCT recipients exhibited significantly more rapid and sustained hematopoiesis (HR 76.92%, 96.15% and 96.15% at 3, 6 and 12months, respectively). The 5-year overall survival (OS) was not different among IST (83.7 ± 4.9%), MSD-HSCT (93.3 ± 6.4%) and HID-HSCT group (80.8 ± 12.3%). Compared with IST, MSD and HID-HSCT demonstrated a trend of superiority in the estimated 5-year failure-free survival rates (93.3 ± 6.4% vs 64.3 ± 6.0%, p = 0.05; 80.8 ± 12.3% vs 64.3 ± 6.0%, p = 0.57). In subsequent stratified analysis on age, we found that HID-HSCT showed its efficacy and safety among young patients. In sum, MSD-HSCT remains first-line treatment choice for HAAA, whereas HID-HSCT represents an alternative treatment choice in addition to IST for young patients (< 40 years) without a matched sibling donor.